Cooking with biomass fuels and mortality among Chinese elderly people: A prospective cohort study. (7th November 2021) - Xu, Minzhi; Ke, Pan; Wang, Chao; Di, Hongkun; Meng, Xin; Xia, Wenqi; Gan, Yong; He, Yan; Tian, Qingfeng; Jiang, Heng; Lu, Zuxun
Abstract: This study used data from the Chinese Longitudinal Healthy Longevity Survey ( n = 9765, age 65+) to investigate the impact of biomass fuels on the mortality of the Chinese elderly population. The association between biomass fuels and mortality was examined using a Cox proportional hazards model. We evaluated the difference in risk of death between those who switched fuel types from biomass to clean fuels and from clean to biomass fuels versus those who did not during the follow‐up period. Participants who used biomass fuels had a higher risk of death than participants who used clean fuels (HR = 1.09, 95% CI: 1.01–1.17). For participants who switched cooking fuel types during the follow‐up period, switching from biomass to clean fuels significantly reduced the risk of death (HR = 0.78, 95% CI: 0.67–0.91), while no evidence of an association between switching from clean to biomass fuels and risk of death was found ( p > 0.05). Interactions and subgroup analyses indicated that effect estimates were greater for women and non‐smokers. Biomass fuels may be associated with a higher risk of death among Chinese elderly. Research measuring personal exposure levels to indoor air pollution caused by biomass fuels combustion is required to confirm our results.